2020
DOI: 10.1093/ckj/sfaa012
|View full text |Cite
|
Sign up to set email alerts
|

Survival of South African patients on renal replacement therapy

Abstract: Background The majority of South Africans rely on a resource-constrained public healthcare sector, where access to renal replacement therapy (RRT) is strictly rationed. The incidence of RRT in this sector is only 4.4 per million population (pmp), whereas it is 139 pmp in the private sector, which serves mainly the 16% of South Africans who have medical insurance. Data on the outcomes of RRT may influence policies and resource allocation. This study evaluated, for the first time, the survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 27 publications
2
18
1
Order By: Relevance
“…This discrepancy exists due to the rationing of government supported RRT in the public sector whilst greater access is available for members of medical insurance schemes in the private sector [11]. Apart from the disparity in access to RRT that exists between public and private healthcare sectors, there are also striking disparities between the different provinces of South Africa, with two provinces (Limpopo and Mpumalanga) having no public sector dialysis centres at all [12].…”
Section: Introductionmentioning
confidence: 99%
“…This discrepancy exists due to the rationing of government supported RRT in the public sector whilst greater access is available for members of medical insurance schemes in the private sector [11]. Apart from the disparity in access to RRT that exists between public and private healthcare sectors, there are also striking disparities between the different provinces of South Africa, with two provinces (Limpopo and Mpumalanga) having no public sector dialysis centres at all [12].…”
Section: Introductionmentioning
confidence: 99%
“…The survival of South African patients on KRT is comparable with that in better resourced countries. Jardine et al 17 recently analysed South African Renal Registry data and reported 1-year survival of 90.4% in incident patients. There was no difference in survival between patients treated in the private and public healthcare sectors, even after using multivariable analysis to adjust for differences in case mix.…”
Section: Discussionmentioning
confidence: 99%
“…The use of PD as the first KRT modality in the public sector has been reported at 57%. 17 PD catheters are often inserted at the bedside and around half of South African nephrologists report competence at this skill. 18 Continuous ambulatory peritoneal dialysis (CAPD) is the predominant form of PD, with most patients performing four 2-litre exchanges per day.…”
Section: Peritoneal Dialysismentioning
confidence: 99%
“…The number of subjects was significant enough when compared to other five-year survival analysis studies based on the registry. [6][7][8][9][10][11] This study analyzed the survival as stratified by age, gender, and underlying kidney disease, which is similar to others . [6][7][8][9][10][11][12][13][14][15][16][17] .…”
Section: Discussionmentioning
confidence: 99%